Uma proposta para automatização do monitoramento da interceptação luminosa em pastagens utilizando uma rede de sensores sem fio de baixo custo - Silva, Victor Ribeiro (2014)
A wireless sensor network was used to monitor the light interception in pastures. The focusoftheworkwastheconstructionofalightmeterlowcostasaalternativetotheLICORLI-1776,high-costequipmentcurrentlyusedbyEmbrapa,andalsotheconstruction ofasensornodethatfunctionedproperlyinpastures,withouttheneedforskilledlaborto operateit. It have been analysed prototypes of luminosity meters of existing low cost and proposed ameter,withitscorrespondingsensor node , suitable low cost. This work presents theoretical and practical studies, implementing two prototypes of sensor nodesusingthephotoelectriccomponentphotodiodeS7686. Tests were performed and evaluated experimentally the performance of a wireless sensor network with star topology. In these tests, the proposed network showed the expected resultsandtheprototypedevelopedshowedsatisfactoryresultswithrespecttothecostof its production.